2014
DOI: 10.5585/podium.v3i1.71
|View full text |Cite
|
Sign up to set email alerts
|

Missão Organizacional: Análise dos Principais Elementos Propostos por Pearce II (1982) Presentes nas Missões dos Hotéis do Sul do Brasil

Abstract: A missão organizacional representa a razão de ser das empresas, para que ela serve, qual sua justificativa de existência para a sociedade e a função social que exerce. Assim, este artigo tem por objetivo analisar os elementos propostos por Pearce II (1982) presentes nas missões dos hotéis do Sul do Brasil associadas à ABIH (Associação Brasileira da Indústria de Hotéis) do Paraná, de Santa Catarina e do Rio Grande do Sul. Para atingir tal objetivo, realizou-se uma pesquisa descritiva, com abordagem quantitativa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
1
5
0
1
Order By: Relevance
“…The highest concentration is in the institutions that describe only 1 or 2 elements, revealing that there is no evolution in the effectiveness of the use of the mission statement. These results are similar to those of Mussoi, Lunkes and Silva, (2011), Teles and Lunkes (2009) and Souza, Coral and Lunkes (2014).…”
Section: A Consolidated Analysissupporting
confidence: 92%
See 2 more Smart Citations
“…The highest concentration is in the institutions that describe only 1 or 2 elements, revealing that there is no evolution in the effectiveness of the use of the mission statement. These results are similar to those of Mussoi, Lunkes and Silva, (2011), Teles and Lunkes (2009) and Souza, Coral and Lunkes (2014).…”
Section: A Consolidated Analysissupporting
confidence: 92%
“…Bartkus and Glassmann (2008) concluded that institutional interests motivate the inclusion of specific stakeholders in the mission statements, and social issues related to political decisions are hierarchically higher than the sustainable and responsible decisions. Souza, Coral and Lunkes (2014) identified that hotels in Southern Brazil do not have an effective mission statement and that the mission statement is used more as an advertising management tool than as a strategic tool.…”
Section: Mission Statements In the Context Of Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…The research conducted by Berbegal-Mirabent et al (2019), Mussoi et al (2011), Pearce (1982), Pearce and David (1987), and Souza et al (2014) sought to identify the necessary components of a mission statement based on analyzing the mission statements of different groups of companies. Standing out among the information identified is that which portrays the concern with survival, growth, and profitability (O'Gorman & Doran, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Realizaram um estudo cujo escopo principal é avaliar de forma objetiva os elementos das missões institucionais das companhias de capital aberto no Brasil (5). E recentemente, (28), realizaram uma pesquisa cujo objetivo era analisar os elementos propostos Pearce II (4) presentes nas missões de hotéis do Sul do Brasil associados à Associação Brasileira da Indústria de Hotéis. Os resultados sugerem que nenhuma empresa da amostra possui uma missão efetiva, ou seja, os hotéis analisados fazem a missão por adequação à sua estrutura ou por influência do setor em que estão inseridos.…”
unclassified